Uncovering new structural insights for antimalarial activity from cost-effective aculeatin-like derivatives. Issue 7 (18th December 2014) - Winkler, Matthias; Maynadier, Marjorie; Wein, Sharon; Lespinasse, Marie-Ange; Boumis, Giovanna; Miele, Adriana E.; Vial, Henri; Wong, Yung-Sing
Abstract : An expedient synthesis of aculeatin-like analogues results in finding PfTrxR as putative cellular target and a promising new antimalarial chemotype. Abstract : A series of new aculeatin-like analogues were synthesized in two steps by combining two sets of building blocks. Many compounds showed inhibitory activities in vitro against Plasmodium falciparum and have helped to gain more insight into structure–activity relationships around the spirocyclohexadienone pharmacophoric scaffold. Plasmodium falciparum thioredoxin reductase (PfTrxR) has been investigated as a putative cellular target. Moreover, a new aculeatin-like scaffold without Michael acceptor properties, efficient at 0.86 μM against P. falciparum 3D7, was identified and raises the prospect of developing a new antimalarial agent.